Assessment of changes in the occurrence of Fusarium toxin and ochratoxin A in Poland related to extreme weather phenomena - Jacek Postupolski; Andrzej Starski; Ewa Ledzion; Jolanta Kurpińska-Jaworska; Małgorzata Szczęsna (National Institute of Public Health - National Institute of Hygiene, 2019)
Background. Mycotoxins - substances harmful to humans, are ubiquitous in the environment. Mycotoxins are generated primarily by Penicilium, Aspergillus and Fusarium genus fungi. Their presence is associated with the unavoidable presence of mold fungi in the environment. The presently observed adverse climatic changes could negatively affect agriculture, causing erosion and loss of organic matter from soil, promulgation of pests and plant diseases, including those originating from pathogenic molds, and also migration of certain mold species into new regions, ultimately creating more favorable conditions for generation of mycotoxins. Objective. The purpose of this work was to investigate contamination of cereals in Poland with Fusarium and ochratoxin A. Elucidating a correlation between precipitation levels in the individual Provinces and reported levels of the investigated mycotoxins, referring to the generally available meteorological databases, would result in more efficient planning of sampling processes and focusing further preventive actions associated with establishing sampling plans for the following years. Material and methods. Investigations were performed on cereal and cereal product samples taken by the official foodstuffs inspection staff. Some 100 samples were taken annually in the 2009-2012 period (357 samples in total). Tests were performed using high performance liquid chromatography coupled with mass spectrometry (HPLC-MS/MS). Precipitation data were obtained from the Central Office of Statistics, based on data received from the Institute of Meteorology and Water Management. Results. Analysis of the influence of precipitation levels during vegetation period on mycotoxin levels in the investigated foodstuffs was performed by associating each recorded content of deoxynivalenol (n=52, corresponding to 14.6% tested samples), zearalenone (n=30, 8.4%), total T-2 and HT-2 toxins (n=21, 5.9%) and ochratoxin A (n=88, 24.6%) above quantification limit with precipitation levels within the Province from which the sample originated. Deoxynivalenol and zearalenone levels show distinct variability corresponding with variability of precipitation levels, well reflecting the reported higher deoxynivalenol and zearalenone levels observed during the rainy years of 2011-2012. Variability in average ochratoxin A levels was not statistically significant. The relatively higher mycotoxin levels in 2009 may result from the heavy rainfall and flooding of 2007-2008. Dependence between the precipitation levels and number of samples showing levels above quantification limit has been also observed for deoxynivalenol. However, a similar analysis made for zearalenone and ochratoxin A does not point to any significant relationship. No data analysis was possible in reference to total T-2 and HT-2 toxins content due to the insufficient number of results available. However, it should be noted that 21% analyzed samples in 2009 contained T-2 and HT-2 levels above the quantification limit, with average of 8.9 μg/kg, whereas in 2010-2012 only one sample of the 263 tested contained contaminants in quantities above the quantification limit. Conclusions. The model used for forecasting presence of mycotoxins in cereals does not allow its practical application during routine generation of official control and monitoring plans on national scale. Notably, tests performed show that exceeding of maximum contamination levels occurred just incidentally, notwithstanding the adverse weather conditions. Further systematic collection of data on mycotoxin contamination of agricultural crops is required for effective continued investigations.